Penggunaan Metafora Disertai Aplikasi Prezi Desktop Terhadap Motivasi dan Prestasi Belajar Matematika Siswa - Eliza, Rivdya; Hayatullah, Jhon William (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The goal of this research are: 1) the learning outcomes of student’s if using methaphor and prezi desktop applications in math learning is better than the learning outcomes of student who did not receive the same treatment on main subject of the circle 2) the learning outcomes of students who have the higher learning motivation better than the learning outcomes of students who have low learning motivation if using methapor and prezi desktop applications 3) the learning outcomes of students with who have higher learning motivation is better than the learning outcomes for student with low learning motivation if it does not use methapor and prezi desktop application in learning 4) there is or not interaction between the learning with different material presentation and learning motivation toward the results of student learning. This research was quasi experiment with 2×2 factorial design. The population in this study was all eighth grade students of Junior Islamic High School of Durian Tarung Padang Academic Year 2015/2016 consists of 6 classes. Samples were taken randomly, so that get first class VIII.3 as experimental group and VIII.2 as the control group. Based on data analysis conclude that learning by using metaphors and prezi desktop applications produce mathematics learning achievement better than learning without using the treatments on the subject matter of the circle. Mathematics achievement of students who have learning motivation high is better than having a low learning motivation either out of the way of presenting the material to use metaphors and Prezi Desktop, or not, and in this study there is no interaction between the learning by presenting different material and motivation learning on student achievement.